2022
DOI: 10.1002/anie.202117676
|View full text |Cite
|
Sign up to set email alerts
|

Back Cover: PDMS with Tunable Side Group Mobility and Its Highly Permeable Membrane for Removal of Aromatic Compounds (Angew. Chem. Int. Ed. 6/2022)

Abstract: Aromatics-permeable membranes ……made from polydimethylsiloxane with tunable side group mobilities are reported by Gongping Liu and co-workers in their Research Article (e202111810). Phenyl groups were introduced as rigid molecular spacers to endow the methyl groups with high mobility and reconstruct the polymer conformation, creating ah ighway for the fast transport of aromatic molecules,a nd thus realizing efficient removal of aromatic compounds from aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…12 PDMS possesses both robust hydrophobicity under harsh operation conditions (chemically stable up to 480 1C in air 15 ) and intriguing (tunable) gas permeable properties (with abundant nanopore pathways for the permeation of the target gas molecules to the MOS surface). 16 Our previous work has indicated that Pt-anchored CCO with abundant Pt single atoms exhibits superior catalytic properties, which facilitates the spillover of molecule-type O 2…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…12 PDMS possesses both robust hydrophobicity under harsh operation conditions (chemically stable up to 480 1C in air 15 ) and intriguing (tunable) gas permeable properties (with abundant nanopore pathways for the permeation of the target gas molecules to the MOS surface). 16 Our previous work has indicated that Pt-anchored CCO with abundant Pt single atoms exhibits superior catalytic properties, which facilitates the spillover of molecule-type O 2…”
mentioning
confidence: 99%
“…PDMS possesses both robust hydrophobicity under harsh operation conditions (chemically stable up to 480 °C in air 15 ) and intriguing (tunable) gas permeable properties (with abundant nanopore pathways for the permeation of the target gas molecules to the MOS surface). 16 Our previous work has indicated that Pt-anchored CCO with abundant Pt single atoms exhibits superior catalytic properties, which facilitates the spillover of molecule-type O 2 − into more active atom-type O − ions (reaction (1)) and dissociation of the H 2 S molecule into a SH radical and H. The catalyzed surface redox reaction (reaction (2)) between SH and O − results in an excellent response under a dry air atmosphere. 12 O 2(ads) + e − ↔ O 2 − (ads) 2SH (ad) + 5O − (ad) → 2SO 2(ad) + H 2 O (ad) + 5e − Herein, an ultra-thin PDMS overlayer has been proposed as a moisture-resistant molecular sieve for a Pt-anchored CCO-based H 2 S chemiresistor.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Efficient recovery of bio-alcohols from biomass fermentation broth has significant environment and economic impacts. 1,2 On the one hand, bio-alcohols as one of the new sustainable energy sources hold the promise of replacing fossil fuels and alleviating environmental pollution. 3,4 On the other hand, they are important raw materials and common solvents in the medical, chemical, and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%